Emblica Officinalis (Indian Gooseberry) Leaves Extract as Corrosion Inhibitor for Mild Steel in 1N HCl Medium - R. Saratha; V. G. Vasudha (E-Journal of Chemistry)
Corrosion inhibition efficiency of acid extract of dry Emblica officinalis leaves for mild steel in 1N HCl medium is investigated in the present study. Experimental methods include weight loss, potentiodynamic polarization and impedance studies. The results indicate Emblica officinalis leaves to be a good corrosion inhibitor of a mixed type and having efficiency of 87.9% at 2% v/v inhibitor concentration. Corrosion inhibition may be due to the spontaneous physical adsorption of the plant constituents on the mild steel surface. Experimental data fitted the Langmuir, Temkin, Freundlich and Flory-Huggins adsorption isotherms.